(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2019)
A brief description of vibration tables with spatial oscillations of a moving frame and comparison of their technological possibilities depending on their constructive execution are given. The methodology for evaluating the technological and structural parameters of the vibration tables is also presented based on the use of a dimensionless complex parameter that enables to evaluate the consumer qualities of the vibrating tables, their technical level and competitiveness during the design and operation stage. The vibrating machines constructive designs schemes, their characteristics and the description of the scope of application are presented, which enables designers and manufacturers to orientate themselves in the variety of currently used vibration machines with spatial oscillations of the moving frame for the formation of the same type of reinforced concrete products.